Fostering scientific integrity and research ethics in a science-for-policy research organisation - Göran Lövestam; Susanne Bremer-Hoffmann; Koen Jonkers; Pieter van Nes (Research Ethics Review)
The Joint Research Centre (JRC) is the European Commission’s in-house science and knowledge service, employing a substantial staff of scientists devoted to conducting research to provide independent scientific advice for EU policy. Focussed on various research areas aligned with EU priorities, the JRC excels in delivering scientific evidence for policymaking and has published numerous science-for-policy reports and scientific articles. Drawing on a scientific integrity statement, surveys among JRC’s research staff, and thematic discussions with JRC’s research leaders, the JRC has developed a comprehensive Scientific Integrity and Research Ethics (SIRE) framework, including instruments, procedures, and guidelines to ensure high standards and independence in its research. Key components of the SIRE framework include a Scientific Integrity Officer, an Editorial Review Board, a Research Ethics Board, and guidelines for responsible conduct of research. This article provides an overview of the JRC’s SIRE framework and how it was developed, emphasising the importance of maintaining independence, integrity, and ethics in scientific research that supports EU policy. The article also discusses potential gaps in the framework and where additional efforts may be needed, comparing with the recent U.S. National Science and Technology Council report on Protecting the Integrity of Government Science.